L’image de l’actrice véhiculée par les romans victoriens et son influence sur son statut social - Muriel Pécastaing-Boissière (Cahiers Victoriens et Edouardiens)
Numerous Victorian novelists had a thorough knowledge of the theatrical world. They often met performers and were even on friendly terms with a number of actresses. As a result, their style was generally strongly influenced by theatrical devices. Furthermore, life backstage was also a recurrent theme in Victorian novels, since it fascinated the middle classes who were their main readers. However, the Victorian novelists’ first hand knowledge of the Theatre and of its performers did not prevent them from elaborating on the prejudiced clichés of the time when working on backstage plots and especially on characters of actresses. Indeed, their readers just loved such entertaining caricatures, for they were in keeping with what they thought of actresses anyway. As a result, actresses often feature in popular Victorian novels. However, this paper is mostly based upon the study of three novels in which actresses are portrayed in a rather typical way : Nicholas Nickleby (1838-1839), by Charles Dickens, Pendennis (1848-1850) by Thackeray and The Tragic Muse (1890), by Henry James.